VITOM 4K 3D Exoscope: A Preliminary Experience in Thyroid Surgery - Kullar, Peter (Cureus, 2021)
Since its introduction in 2008, the Karl Storz 4K 3D VITOM® exoscope (Karl Storz SE & Co. KG, Tuttlingen, Germany) has been successfully used in various surgical disciplines. This paper describes our department’s experience using this technology and its use in the first total thyroidectomy case. The set up of the 3D VITOM exoscope in the operating theatre allows for a user-friendly approach to thyroid surgery with the exoscope placed out of the line of sight of the surgeon with a monitor placed directly ahead. The surgeon has a control panel within reach, which allows for adjustments to image magnification and focus. The use of the 3D VITOM exoscope has the potential to confer significant improvements in patient outcomes by promoting efficient and safer surgery through superior operative visualisation.